A 2017 Social Accounting Matrix for Chile - Alonso Gonzalez Marentis; Jonas Luckmann; Khalid Siddig (Humboldt-Universität zu Berlin, Faculty of Life Sciences, Department of Agricultural Economics, 2021)
A detailed Social Accounting Matrix (SAM) for Chile is developed for the year 2017. The main data source for developing the SAM is the Central Bank of Chile, from which a 2017 Inputoutput Table (IOT), the national accounts and the Integrated Economic Table (IET) are obtained. Additional sources are used to disaggregate the accounts for the SAM, including household and labor surveys. The developed SAM includes 24 activities, 37 commodities, three production factors (capital and two types of labor classified by skill level), enterprises, households (disaggregated to five income quintiles), the government, 4 types of taxes, investment, stock changes, margins, and rest of the world. To allow detailed representation of the agricultural sector, agriculture is disaggregated into 12 activities and 24 commodities, while industry and services are represented by three and 9 subsectors, respectively.
Keywords: E16; 330; social accounting matrix; copper; agriculture; Chile